Cationic fluorinated micelles for cell labeling and 19F-MR imaging - Jirát-Ziółkowska, Natalia; Panakkal, Vyshakh Manayath; Jiráková, Klára; Havlíček, Dominik; Sedláček, Ondřej; Jirák, Daniel (Scientific reports, 2024)
Magnetic resonance imaging (MRI) relies on appropriate contrast agents, especially for visualizing transplanted cells within host tissue. In recent years, compounds containing fluorine-19 have gained significant attention as MRI probe, particularly in dual 1H/19F-MR imaging. However, various factors affecting probe sensitivity, such as fluorine content and the equivalency of fluorine atoms, must be considered. In this study, we synthesized fluorinated micelles with adjustable surface positive charge density and investigated their physicochemical properties and MRI efficacy in phantoms and labeled cells. While the micelles exhibited clear signals in 19F-MR spectra and imaging, the concentrations required for MRI visualization of labeled cells were relatively high, adversely affecting cell viability. Despite their favourable physicochemical properties, achieving higher labeling rates without compromising cell viability during labeling remains a challenge for potential in vivo applications.
Keywords: halogenace; zobrazování fluorovou magnetickou rezonancí; viabilita buněk; micely; Fluorinated micelles; magnetická rezonanční tomografie; kontrastní látky; Halogenation; 19F magnetic resonance spectroscopy; Cell Survival; kationty; fantomy radiodiagnostické; Cations; Fluorine-19 Magnetic Resonance Imaging; 19F magnetic resonance imaging; Animals; lidé; Micelles; Contrast Media; Humans; zvířata; fluor; barvení a značení; myši; Phantoms, Imaging; Fluorine; Staining and Labeling; Magnetic Resonance Imaging; Cell labeling; Mice